Demagoguery, Charismatic Leadership, and the Force of Habit. Issue 3 (27th May 2019) - Roberts-Miller, Patricia
Abstract : This essay argues that scholars who focus on demagogues rather than demagoguery are mistakenly making charismatic leadership a necessary quality of demagoguery. Instead of focusing on demagogues, we should focus on the conditions that nurture demagoguery. This essay makes the case that charismatic leadership is not necessary for demagoguery but an almost inevitable method of gaining compliance in a culture that promotes outcomes-based ethics.